Senkyo . Campaign! The Kawasaki Candidate - Soda, Kazuhiro (Kazuhiro, Soda, 2007)
Verzio FF In the fall of 2005, 40-year-old, self-employed Kazuhiko “Yama-san” Yamauchi’s peaceful, humdrum life was turned upside-down when Liberal Democratic Party selects him at the last minute as its official candidate for a place on the Kawasaki city council. With zero experience in politics and without the support of voters, Yamauchi has one week to prepare for an election critical to the future of the party and his own life. He visits social events, meetings with pensioners, bus stations and stops, shaking hands with all he meets. Can a candidate without either political experience or charisma win in elections? The film presents a humorous view of political strategy, values and tradition in contemporary Japanese society.